Deposição de DNA no fígado como um mecanismo acessório para o controle da infecção sistêmica - Rafaela Vaz Sousa Pereira (2016)
The liver is essential for maintaining body homeostasis. Among its various physiological functions, the liver plays an important role in detection and removal of pathogens from the circulation, being a major organ in the host / microbiota interaction. The liver macrophages (Kupffer cells) play a key role in the capture of circulating pathogens, but there should be accessory mechanisms acting in emergency situations such as systemic infection. In this context, DNA is known to be a molecule with antimicrobial activity, and this function has been evolutionarily conserved and retained in several species. Considering this, our goal was to determine whether a systemic infection could induce the release of DNA in the liver and to determine the consequences of intrahepatic DNA deposition during infection. As expected, we demonstrated there is a widespread DNA deposition within the liver during polymicrobial sepsis, which progressed through the course of infection. Our data indicates that such accumulated DNA was not derived from neutrophils (NETS) or from necrotic hepatocytes, since we did not observe hepatocyte death during sepsis. Enzymatic removal of DNA during disease caused a significant increase in bacteremia at late timepoints of infection, however, no influence on the inflammatory response was observed. Taken together, our data demonstrate there is deposition of DNA in the liver during sepsis, possibly deriving from viable hepatocytes, which could be acting as an additional mechanism for controlling bacterial spread during systemic infection.